Features of biochemical changes in patients with localized scleroderмa - Ata, Mohamed Abbas (ScienceRise: Medical Science, 2019)
The aim of the study was to determine the characteristics of biochemical changes in localized scleroderma based on the analysis and evaluation of dysmetabolic disorders of homeostasis from the standpoint of the individual characteristics of patients. Materials and methods. Under our supervision there were 107 patients with localized scleroderma in the acute stage who were hospitalized in the Department of Dermatology of the State Institution “Institute of Dermatology and Venereology of the National Academy of Medical Sciences of Ukraine” from 2014 to 2018. All patients were randomly assigned to 3 groups comparable in all parameters — the main group and two comparison groups. The main group consisted of 33 (34.01 %) localized scleroderma patients who received complex treatment; in the І group - 34 (35.05 %) patients who received only traditional therapy; in group II - 30 (30.92 %) patients who received treatment according to the scheme, which included traditional therapy with the addition of thiotriazoline. The study of the concentration of C-reactive protein (CRP) was performed by quantitative immunoturbidimetry according to OP. Shevchenko (1997); serum protein fractions - by electrophoresis on agarose gel plates by the method of S.S. Chernecky, V.J. Berger (2008); total lipids - by V.N. Titovu, M.G. Tvorogova (1992); high-density lipoproteins, triglycerides, beta-lipoproteins - by S.E. Severin (1977);cholesterol concentration - according to D. Vaidya (2005); the atherogenic coefficient was calculated by the formula: CA = (total cholesterol - HDL) / HDL); determination of serum magnesium and chlorine using colorimetric analysis (A.Sh. Byshevsky, OA Tersenov, 1994). Results. In the studied groups of patients with OSD and in healthy donors, a study was made of the level of C-reactive protein (CRP., The concentration of which in patients with OSD in the exacerbation stage reached 44 g / l before treatment, after conducting a course of appropriate drug therapy in each study group amounted to: in group II, the comparison group — 38 g / l, in group I, the comparison group — 30 g / l, and in the main group — 16 g / l, which are closest to the level of CRP in healthy donors and indicate high efficacy of the treatment we developed a scheme with the inclusion of modern drugs. In the serum of patients of the I and II comparison groups, there was an increase in magnesium content by 1.8 times and a decrease in chlorine level by 1.2 times, which characterizes the presence of deep metabolic disorders in this category of patients, affecting not only immunoreactivity but also water-electrolyte metabolism. The magnesium content and the level of chlorine in the blood serum of the patients of the main group did not significantly differ from the control and was 2 times lower in comparison with the concentration of these indicators in the group of patients with SJD before treatment Concentration of cholesterol was lower in the OSD group before treatment and in the comparison groups - an average of 1.8 times. Also noted increase in the concentration of high density lipoprotein - an average of 2.7 times. The concentration of triglycerides was minimal in the CSF group before treatment and was 0.4 ± 0.03 mol / L, which was 5.4 times lower in the control group of healthy donors and 4 times lower than in the main group of patients. Conclusion. Based on the conducted research, a number of features of biochemical parameters were revealed, which indicate that localized scleroderma is accompanied by disturbances of the biochemical link of homeostasis. The change in the ratio of lipid and protein fractions indicates a violation of the regulatory and regenerative functions at the level of the structural organization of cell membranes, and an increase in the magnesium content and a decrease in the level of chlorine — deep metabolic disorders in this category of patients